The natural evolution of untreated deep endometriosis and the effect of hormonal suppression: A systematic literature review and meta‐analysis - Veronica Bandini; Francesca Giola; Deborah Ambruoso; Sonia Cipriani; Francesca Chiaffarino; Paolo Vercellini (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Peritoneal infiltrating and fibrotic endometriosis, also known as deep endometriosis, is the most severe manifestation of the disease that can cause severe complications including bowel and ureteral stenosis. The natural history of these lesions and the possible effect of hormonal treatments on their progression are undefined. Therefore, we conducted a systematic review and meta‐analysis to investigate whether and how frequently deep endometriosis progresses over time without or with ovarian suppression. This could inform management decisions in asymptomatic and mildly symptomatic patients. Material and Methods For this pre‐registered systematic review (CRD42023463518), the PubMed and Embase databases were screened, and studies published between 2000 and 2023 that serially evaluated the size of deep endometriotic lesions without or with hormonal treatment were selected. Data on the progression, stability, or regression of deep endometriotic lesions were recorded as absolute frequencies or mean volume variations. Estimates of the overall percentage of progression and corresponding 95% confidence intervals were calculated using a random‐effect model. When studies reported lesion progression as pre‐ and post‐treatment volume means, the delta of the two‐volume means was calculated and analyzed using the inverse variance method. Results A total of 29 studies were identified, of which 19 studies with 285 untreated and 730 treated patients were ultimately selected for meta‐analysis. The overall estimate of the percentage of lesion progression in untreated individuals was 21.4% (95% CI, 6.8–40.8%; I2 = 90.5%), whereas it was 12.4% during various hormonal treatments (95% CI, 9.0–16.1%; I2 = 0%). Based on the overall meta‐analysis estimates, the odds ratio of progression in treated vs untreated patients was 0.52 (95% CI, 0.41–0.66). During hormonal suppression, the mean volume of deep endometriotic lesions decreased significantly by 0.87 cm3 (95% CI, 0.19–1.56 cm3; I2 = 0%), representing −28.5% of the baseline volume. Conclusions Untreated deep endometriotic lesions progressed in about one in five patients. Medical therapy reduced but did not eliminate this risk. Given the organ function failure potentially caused by these lesions, the decision whether to use hormonal treatments in asymptomatic or mildly symptomatic women should always be shared, carefully weighing the potential benefits and harms of the two alternatives after extensive counseling.